Haven Point - Hume, Virginia (St. Martin's Press, 2021)
"A sweeping debut novel about the generations of a family that spends summers in a seaside enclave on Maine's rocky coastline. In 1944, Maren Larsen is a blonde beauty from a small Minnesota farming town, determined to do her part to help the war effort--and to see the world beyond her family's cornfields. As a cadet nurse at Walter Reed Medical Center, she's swept off her feet by Dr. Oliver Demarest, a handsome Boston Brahmin whose family spends summers in an insular community on the rocky coast of Maine. Maren soon discovers that the residents of Haven Point are skeptical of newcomers, and their quick wartime marriage raises eyebrows. Although the chilly reception gives her pause, Maren can't deny the charm of the old house on the cliff, and she vows to make Oliver's family her own. But during the summer of 1970, tragedy strikes otherwise idyllic Haven Point--and in the aftermath, Oliver and Maren's seventeen-year-old daughter, Annie, vows never to return. Nearly fifty years later, Maren's granddaughter, Skye, has arrived in Maine to help scatter Annie's ashes. Maren knows that Skye inherited her mother's view of Haven Point, and that she finds the place--and the people--snobbish and petty. But she also knows that Annie never told her daughter the whole truth about what happened that fateful summer. Over seven decades of a changing America, through wars and storms, betrayals and reconciliations, Haven Point explores what it means to belong to a place, and to a family, which holds as tight to its traditions as it does its secrets"--